2018
DOI: 10.1155/2018/2429160
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Glutamyltransferase and Risk of Acute Coronary Syndrome in Young Chinese Patients: A Case-Control Study

Abstract: Background Serum gamma-glutamyltransferase (GGT) is a biomarker of hepatic disease. Recent studies have shown that GGT may also associate with the risk of coronary artery disease. However, the underlying mechanisms of this association are still unclear. Methods This study included 216 young patients with acute coronary syndrome (aged ≤55years) and 227 age-matched controls with normal findings by coronary angiography or coronary computed tomography angiography. We use standard colorimetric techniques and sandwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
2
6
1
Order By: Relevance
“…Serum GGT is a widely used marker for fatty liver disease and alcohol consumption and is associated with an increased risk of CAD [29]. Huang et al reported that GGT was associated with the risk of ACS in relatively young patients [8]. In the current study, GGT was associated with CAD in young patients according to the Mann-Whitney U test, but not significantly associated with CAD by univariate analysis.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…Serum GGT is a widely used marker for fatty liver disease and alcohol consumption and is associated with an increased risk of CAD [29]. Huang et al reported that GGT was associated with the risk of ACS in relatively young patients [8]. In the current study, GGT was associated with CAD in young patients according to the Mann-Whitney U test, but not significantly associated with CAD by univariate analysis.…”
Section: Discussioncontrasting
confidence: 42%
“…In order to provide earlier and better diagnosis of CAD in young adults, novel risk factors and markers have been evaluated in the literature [6][7][8]. However, these studies included specific cohorts, such as ACS [6][7][8][9]. Therefore, we aimed to investigate the relationship between traditional and nontraditional risk factors and the presence of significant atherosclerosis in a young population with SAP.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, they demonstrated in multivariate analysis that serum GGT activity was an independent predictor of in-hospital MACE (odds ratio (OR) 1.12, 95% confidence interval (CI) 1.01-1.33; p < 0.001) [32]. These results agree with those of others who confirmed the prognostic value of GGT in long-term follow-up [33,34].…”
Section: Discussionsupporting
confidence: 79%
“…Hemoglobin, FBG, HbA 1c , total cholesterol (TC), triglycerides, low-density lipoprotein-C (LDL-C), high-density lipoprotein cholesterol, serum creatinine, highsensitivity C-reactive protein (hs-CRP), and N-terminal pro-Btype natriuretic peptide (NT-proBNP) levels were detected. LDL-C was calculated using the Friedewald equation (17,18). TyG index was calculated using the following: Ln [fasting triglycerides (mg/dL) × FBG (mg/dL)/2] (5).…”
Section: Baseline Characteristics Tyg Index Detection and Cmr Examinationmentioning
confidence: 99%